Assessing changes in running kinematics at different intensities: a case study - Bernans, E. (Journal of Physical Education and Sport, 2023)
This study aimed to evaluate individual variations in running kinematics at various running intensities by considering the potential differences in runners' abilities. It is essential to recognize that running kinematic dynamics may not remain identical at different intensities, even among runners with similar performance abilities. To avoid assumptions based solely on group data, this study focused on individual variations as a key objective. The research involved three male runners who demonstrated similar 3000 m running times, ranging from 9:02 to 9:08 min. These participants underwent a series of running tests on a leveled treadmill, during which comprehensive measurements of running kinematics, heart rate, and blood lactate values were recorded. The running velocity was in the range of 12-20 km/h, and nine individual tests were conducted with a randomized order of velocities. Analysis of the heart rate data revealed variations in exercise response both within and between individuals. However, among these three runners, general physiological responses, including the heart rate and lactate concentration, were similar. This study shows that running velocity significantly affects various kinematic characteristics of running such as the step length, step frequency, contact time, and flight time. The findings indicate that with an increase in the running velocity, there is a corresponding increase in the step length and stride frequency, a decrease in the contact time, and an increase in the flight time. Furthermore, a strong positive correlation between the step length and running velocity is observed; there is also a general trend of stride frequency increasing with higher running velocity, although this result is not always statistically significant. In conclusion, this study highlights the importance of considering individual variations in running kinematics when assessing the effects of different running intensities.